Company Covid-19 vaccination: whether refusal by employee justifies termination? - Ali Mohamed, Ashgar Ali; Amirnuddin, Puteri Sofia; Ahmad, Muhamad Hassan (2021)
Workers’ safety and health at the workplace is the duty placed on the employer and the breach thereof could expose them to penal sanctions under the occupational safety and health law and with potential civil liability for negligence. The Coronavirus outbreak (Covid-19) with the government’s interstate and inter-district travel restrictions on the advice of the Malaysian National Security Council had seen many companies operating with minimum force with many staff ordered to work from home. The distribution of Covid-19 vaccine recently would surely come as a relief for businesses and the employers. To ensure covid free workplace, employers are now requiring all their employees’ to be vaccinated before they return to the workplace. Unfortunately, a handful workers are refusing vaccination due to several reasons such as the efficacy of the vaccine, its side effects especially for those with pre-existing medical conditions and for fear of its potential side-effects, among others. As there is no law mandating the vaccination, the issue arises as to whether the employer can force their employees to be vaccinated before allowing them to return to work or as soon as the vaccination for them is made available. Whether refusal by the employee to comply with the management request for vaccination can be a basis for terminated from employment. Recently, the Inspector-General of Police (IGP) had said that the police officers who refuses to take the Covid-19 vaccine will be asked to resign. The question will then arise whether such a departure was voluntary resignation or a dismissal from employment. It is important to consider whether the employee’s refusal to comply with the management’s request was based on legitimate reasons. Hence, this article discusses the above issues with reference to workers in the private sector. At this juncture, it is noteworthy that an employee’s right to decline vaccination need to be balanced against the employer’s obligation to provide a safe and healthy work environment. In this regard, workers who refuses vaccination otherwise than the pre-existing medical conditions could potentially risk others at the workplace of this disease and hence, undermining the employer’s workplace safety and health obligation.